Commercially-owned Social Media Spaces and the Future of the Open Web: Implications for Academic Librarians - Lilburn, Jeff (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Explores the meanings and implications of academic libraries' presence within commercially-owned social media spaces such as Facebook. Considers the apparent contradiction between librarians' work to defend the commons and their participation in social media spaces that are, arguably, part of a process to enclose the commons and privatize the Internet. Cette communication explore la signification et les implications de la présence des bibliothécaires en milieu universitaire sur les réseaux sociaux privés tels que Facebook. L’auteur illustre l’apparente contradiction entre le travail des bibliothécaires qui défend le bien commun et leur participation dans les réseaux sociaux qui, tel qu’argumenté, font partie d’un processus visant à réduire la portée du bien public et à privatiser Internet.